PROTEINS OF THE ERYTHROCYTE MEMBRANE AND METABOLIC SYNDROME - A. S. Sergeyeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
There is no literature data on the changes of structural and functional qualities of the erythrocyte membrane at the arterial hypertension (AH) complicated and non-complicated by the metabolic syndrome (MS). Although the changes of interrelation between the proteins of erythrocyte membrane at the AH can influence the deformability of the membrane itself. The aim of the work was to estimate the peculiarities of interrelation between the proteins of erythrocyte membrane in the patients with arterial hypertension complicated and non-complicated by the metabolic syndrome. The research included 51 men with AH and 29 clinically healthy men which were divided into 3 groups: group 1 - control; group 2 - men with AH complicated with MS (n = 29); group 3 - men with AH non-complicated with MS (n = 22). We studied blood lipids, biochemical and hemostasiological parameters, assessed 10 proteins of erythrocyte membrane. Patients of the 2nd and 3rd groups had different content of α- and β-spectrins, anion-transport protein (ATP), plates 4.1, glycerol-3-phosphatededehydrogenase (G-3-PDG), glutathione S-transferase (GST). The results of the research showed that metabolic syndrome at the AH can not only influence the state of vessel wall but also cause significant disorders of structural and functional qualities of the erythrocyte membrane.